패션 리테일 샵에 나타난 복합문화공간 구성 특성에 관한 연구 - 김중희; Joong Hee Kim; 김국선; Kook Sun Kim; 이정민; Jung Min Lee (기초조형학연구, 2015)
현대 패션 리테일 샵은 소비자의 라이프스타일의 변화와 가치 추구 니즈에 따라 단순히 상품을 판매하는 공간을 넘어 감성, 문화, 경험을 즐길 수 있는 공간으로 변화하고 있다. 패션 리테일 샵 내의 문화공간은 패션소비를 위한 방문자뿐 아니라 일반 대중이 여러 문화 활동을 한 곳의 장소에서 손쉽게 즐기고 참여할 수 있어 기존의 단일적 패션 샵이나 단순한 문화공간과 차별되는 새로운 공간으로서, 현재의 다양하고 문화적 요구를 충족시키는 복합적인 공간으로 도약하고 있다. 현재 국내에는 수입 패션 브랜드와 국내 대기업에서 운영하는 패션 브랜드의 플래그십 샵을 중심으로 패션 샵과 함께 까페나 갤러리, 공연장 등의 문화공간을 구성하며 나타나고 있지만, 아직 패션 카테고리의 구성 기준이 모호하고, 복합문화공간으로서 구성적 특성이 명확하지 않다. 따라서 본 연구는 패션 리테일 샵에 나타난 복합문화공간 개념을 정립하고, 공간의 구성적 특성을 규명하는데 연구의 목적이 있다. 연구방법으로 패션 리테일 샵과 플래그십 샵, 복합문화공간의 이론적 고찰과 선행연구, 문헌자료 조사를 통해 분석 기준틀을 구축하였고, 사례 공간의 현장 방문을 통해 구성 특성을 분석하였다. 연구 결과로서 첫째, 패션 리테일 샵의 복합문화공간은 잡화와 의류를 중심으로 패션 제품의 구성 비중이 높으며, 브랜드 컨셉과 연계되는 리빙, 디자인 용품의 카테고리가 복합적으로 구성되는 특성이 나타났다. 둘째, 판매 이익이 중요시되는 리테일 샵의 특성상 판매공간의 구성 비중이 가장 높았으며, 문화공간은 교육형 체험 프로그램이 적어 비중이 낮게 나타났고, 대중의 참여 프로그램이 많은 기업이나 공공기관의 문화공간과는 차별성을 보였다. 셋째, 브랜드 아이덴티티를 공간 디자인을 통해 표현하고, 브랜드의 역사와 추구하는 예술가치, 패션 트렌드 정보를 문화공간을 통해 제공하는 특성을 보였으며, 패션과 문화가 협업되어 새로운 패션문화 쇼핑공간을 만들고, 이를 통해 브랜드 이미지를 높이는 플래그십 샵으로서 브랜드의 전략적인 마케팅 공간임을 알 수 있었다. 이처럼 패션 리테일 샵의 복합문화공간은 이 시대의 패션과 문화 트렌드를 가장 잘 반영하는 곳으로서 앞으로도 패션과 함께 다양한 예술, 교육체험 문화의 여러 분야를 복합적으로 구성하여 대중의 참여를 높이는 다양한 새로운 형태의 문화공간이 구축되기를 기대한다. As a follow-up for the change of consumers` lifestyle and a need of seeking values, modern retail shops has been changing from just a space for sales to a room for gaining emotion, culture, and experience. Because culture zones in the fashion retail shops differ from ordinary fashion shops and regular cultural zones by allowing customers to participate in plenty of cultural activities, they are becoming a complex place that can accommodate various cultural needs, In Korea, it is shown in flagship shops, mostly propelled by overseas fashion brands and domestic corporations. However, it is uncertain to set up a standard for fashion categories, and the concept of compositional cultural complex is vague to define. Therefore, this research is to certify the concept of cultural complex, and define the characteristics of organization of space. As a research method, we`ve founded the standard of analysis by considering the theory of fashion retail shops, flagship shops, and cultural complexes. Additionally, we`ve made a conclusion by analyzing the characteristics of cultural complexes that are inside fashion retail stores. In conclusion, cultural complexes consist of diverse commercial spaces. Moreover, it has a characteristic that profit of the brand is the priority, making public facilities are smaller than shopping sites. Allowing customers to acknowledge brand identity, and facilitating customers to experience the history of brand and the pursuit for artistic values, shows the distinguishing point between cultural complexes constructed by fashion retail shops. However, education-related factors scored lower than other factors. Therefore, it has to develop a program that is unique for fashion. Cultural complexes provide diverse shopping experiences to customers, which plays a role of flagship shops. It is also anticipated to be a diverse, culture-combined area.